Partai Politik Lokal di Negara Kesatuan: Upaya Mewujudkan Otonomi Daerah di Bidang Politik - M. Rifqinizamy Karsayuda (Jurnal Hukum IUS QUIA IUSTUM, 2010)
A district autonomy as the consequence of UUD 1945 amendment, gives several authorities to the local government, and one of the autonomies is in politics. The local politic parties are expected to be able to apply the political autonomy, even though juridically its existence is still difficult to be conducted by the national party regulation in UU Nomor 2 Tahun 2008 (constitution number 2 year of 2008) about Political Party and UU Nomor 10 Tahun 2008 (constitution number 10 year of 2008) about Public Election. The focuses of this research are; first, what is the theoretical basis in creating the local political party in Indonesia as a united nation? Second, how is the concept of local political party that is relevantly applied in Indonesia as a united nation which is suitable with Indonesian constitutional substance? The method used in this research is the qualitative investigation of law material with the juridical approach which is completed by political approach. This research has concluded; first, the urge of local political party has presented in Indonesia, not only as the consequence of the realization of district autonomy, but also as the implementation of ideology federalism theory which is aimed as the existence guard of a country.Second, a local political party that can be developed in Indonesia, in the future, is a political party that has no relation with a national party, as it is a structure as well as in election.Key words : Local autonomy, unitarian state, local poltical party